2021
DOI: 10.3390/nu13103346
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Potential Hepatoprotective Effect of Myo-Inositol and Its Influence on Zebrafish Development

Abstract: Inositol is a natural substance found widely in plants. It is used in therapies for many medical cases. The aim of this study was to determine the toxicity of myo-inositol (MI) and to investigate its potential hepatoprotective character. In the first part of the study, zebrafish embryos were incubated with 5, 10, 20, 40, 60, 80, and 100 mg/mL MI. Endpoints such as survivability, hatching rate, malformation, and mobility were evaluated. Our results demonstrated that the high doses of MI lead to increased mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In this study, we used concentrations of MI with a maximum value of 40 mg/mL. Based on our previous research, in which we conducted the fish embryo toxicity (FET) test, MI concentrations higher than 40 mg/mL turned out to be toxic and led to significant disturbances in zebrafish maturation and survivability [1]. In another research paper found in online databases, the authors investigated the impact of MI on stress reduction in another fish species-the turbot (Scophthalmus maximus).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used concentrations of MI with a maximum value of 40 mg/mL. Based on our previous research, in which we conducted the fish embryo toxicity (FET) test, MI concentrations higher than 40 mg/mL turned out to be toxic and led to significant disturbances in zebrafish maturation and survivability [1]. In another research paper found in online databases, the authors investigated the impact of MI on stress reduction in another fish species-the turbot (Scophthalmus maximus).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclitols are a group of compounds that may have a beneficial effect on human health and support immunity against numerous diseases, but its use as a clinical therapeutic is not established. Also known as sugar alcohols or polyols, they are widely distributed in the environment, and are found in many organic products such as citrus fruits, nuts, yeast, grains, beans, buckwheat, and many others [1]. Cyclitols and their derivatives perform many functions in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery is significant as it supports the prospective use of SCI as an antiepileptic drug. Zebrafish larva motility may increase in SCI groups either due to SCI directly connecting to GABA-A receptors or indirectly through SCI metabolites, most likely through binding to excitatory receptors in the brain [28].…”
Section: Discussionmentioning
confidence: 99%